Does total hip arthroplasty benefit patients with minimal radiological osteoarthritis? - Kartik Logishetty; Jeroen C. F. Verhaegen; Shannon Tse; Tim Maheswaran; Max Fornasiero; Hariharan Subbiah Ponniah; Jonathan B. Hutt; Johan D. Witt (Bone & Joint Open, 2025)
Aims: The effectiveness of total hip arthroplasty (THA) for patients with no or minimal radiological signs of osteoarthritis (OA) is unclear. In this study, we aimed to: 1) assess the outcome of such patients; 2) identify patient comorbidities and CT or MRI findings which predicted outcome; and 3) compare their outcome to the expected outcome of THA for hip OA. Methods: Adult patients undergoing THA for hip pain, with no or minimal radiological features of OA (Tönnis grading scale ≤ 1), were identified from a consecutive series of 1,925 THAs. Exclusion criteria were: inflammatory arthritis; osteonecrosis of the femoral head; prior trauma or infection; and patients without minimum one-year follow-up and patient-reported outcome measures (PROMs). The primary outcome measure was the Oxford Hip Score (OHS). Secondary outcome measures were EuroQol-visual analogue scale (EQ-VAS), University of California and Los Angeles (UCLA) scale, and patient satisfaction on a validated three-point ‘better’, ‘same’, or ‘worse’ scale. Results: A total of 107 patients with a median age of 41 years (IQR 18 to 73) were included, with mean follow-up of 6.0 years (SD 3.1). All patients underwent a diagnostic hip injection as a decision aid. Median postoperative OHS was 34 (IQR 28 to 42), with 36 patients (33%) achieving a patient-acceptable symptom state (OHS ≥ 42), lower than THA patients in international registries (40 to 43 points). Secondary outcomes were UCLA of 6 (4 to 8) and EQ-VAS of 73 (51 to 80); 91/102 patients (89%) felt ‘better’ and would ‘undergo surgery again'. Patients with chronic pain syndrome or hypermobility had lower OHS than patients without comorbidities (-6 points, p < 0.006). Overall, 84 patients had a CT and 34 patients an MRI. Patients with subchondral cysts (OHS 42 (37 to 45) vs 35 (26 to 36); p = 0.014) or joint space narrowing on CT (OHS 42 (IQR 37 to 44) vs 35 (26 to 36); p = 0.022) had higher function. Conclusion: Despite high satisfaction levels, patients undergoing THA with minimal or no radiological OA had lower postoperative function than typical THA patients. We recommend obtaining low-dose CT imaging and a diagnostic hip injection to aid decision-making. Cite this article: Bone Jt Open 2025;6(3):328–335.